2011
DOI: 10.1007/s10340-011-0396-8
|View full text |Cite
|
Sign up to set email alerts
|

Lethal and sub-lethal effects from short-term exposure of Rhyzopertha dominica on wheat treated with Storicide II®

Abstract: Hard red winter wheat was treated at 0 (untreated control), 25, 50, 75, and 100% of the label rate of the insecticide Storicide II Ò , which is chlorpyrifosmethyl and deltamethrin applied at label rates of 3 and 0.5 ppm, respectively. Paired male and female Rhyzopertha dominica F., the lesser grain borer, were exposed at 27°C and 60% RH on wheat treated at each of the five rates above for 2, 4, 8, 16, or 32 h, and then transferred to untreated wheat and held for 1 week at the same environmental conditions. Aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…In comparison with female A. lucorum, males were sensitive to all of the insecticides tested, and there were differences in their sensitivity to different insecticides (Table 3). Previous studies with different insecticides also showed differential susceptibility between the sexes of tested insects (López et al 2008;Arthur 2012). It was suggested by Zhang (1988) that females were less sensitive to organophosphates and carbamates than males owing to the lower quantity of acetylcholinesterase in females.…”
Section: Discussionmentioning
confidence: 83%
“…In comparison with female A. lucorum, males were sensitive to all of the insecticides tested, and there were differences in their sensitivity to different insecticides (Table 3). Previous studies with different insecticides also showed differential susceptibility between the sexes of tested insects (López et al 2008;Arthur 2012). It was suggested by Zhang (1988) that females were less sensitive to organophosphates and carbamates than males owing to the lower quantity of acetylcholinesterase in females.…”
Section: Discussionmentioning
confidence: 83%
“…A study conducted by Arthur (2012) where R. dominica adults were exposed to wheat treated at 0, 25, 50, 75, and 100% of the label rate of a mixture of chlorpyrifos-methyl (3 ppm) and deltamethrin (0.5 ppm) for 2, 4, 8, 16, or 32 h showed that parental adult mortality increased as the concentration and exposure interval increased. Similarly, for progeny production that was assessed after 7 wk, it decreased with increasing concentration of chlorpyrifos-methyl ϩ deltamethrin mixture and increasing exposure time.…”
Section: Discussionmentioning
confidence: 99%
“…It remains unclear, however, if the insects that have been exposed for short periods to chlorfenapyr will die even after their removal from the treated substrate, or a continuous contact with the treated surface is needed to obtain high levels of mortality. It is not clear if the absence of knockdown with non-neurotoxic insecticides also leads to increased survival [ 4 , 21 , 26 ]. Additional experimentation is needed with chlorfenapyr, but also with other non-neurotoxic insecticides, to examine if short exposures without knockdown leads to delayed mortality after the removal from the treated substrate.…”
Section: Discussionmentioning
confidence: 99%
“…However, the authors noted that seven days after the removal of the exposed individuals from the treated grains, adults began to recover from knockdown. Similarly, Arthur [ 4 ] conducted studies by exposing adults of R . dominica on wheat treated with a mixture of chlorpyriphos-methyl and deltamethrin, and noted increased survival and recovery after the removal of the exposed adults from the treated commodity.…”
Section: Introductionmentioning
confidence: 99%